History and Therapeutic Use of MAO-A Inhibitors: A Historical Perspective of MAO-A Inhibitors As Antidepressant Drug - Yanez, Matilde; Fernando Padin, Juan; Alberto Arranz-Tagarro, Juan; Camina, Mercedes; Laguna, Reyes (Current Topics in Medicinal Chemistry, 2012)
Since the first generation of MAO inhibitors was developed, more than fifty years ago, this family of drugs has been ups and downs over the last decades. Actually, interest in MAO inhibitors is reviving and the emergence of new advances in the rational design of molecules and new techniques to predict the in vivo behavior has encouraged the research for new drugs with therapeutic potential in this area. The classic MAOIs have been widely used as antidepressants during the two decades after its introduction in clinic. Based on observations made on MAO inhibition by these drugs, it has been postulated hypothesis that have contributed to a better understanding of the mechanism and management of depressive disorders. However, exaggerated concerns about food and drug interactions relegated these drugs from the pharmaceutical landscape. The correct interpretation and the contextualization of side effects and the recent research findings, in which MAO selective inhibitors appear as promising agents in the treatment of emerging and high prevalence diseases, are placing these drugs again into the scientific and pharmacological focus.
Keywords: iproniazid